2016
DOI: 10.1093/jac/dkw270
|View full text |Cite
|
Sign up to set email alerts
|

IFN-free therapy for HIV/HCV-coinfected patients within the liver transplant setting

Abstract: IFN-free regimens are effective and well tolerated in HIV/HCV-coinfected patients within the LT setting, but more data are needed to confirm our promising results and to establish the best treatment option in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Grant et al found an SVR rate of 87% in eight patients with recurrence of mild hepatitis C treated with a SOF‐based combination. Campos‐Varela et al reported a 100% SVR in two HCV/HIV‐coinfected patients with recurrence of hepatitis C. Similarly, we reported a 100% SVR in seven patients with severe hepatitis C, four of whom had decompensated cirrhosis . Castells et al reported 100% SVR in six HCV/HIV‐coinfected patients treated with SOF + DCV.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Grant et al found an SVR rate of 87% in eight patients with recurrence of mild hepatitis C treated with a SOF‐based combination. Campos‐Varela et al reported a 100% SVR in two HCV/HIV‐coinfected patients with recurrence of hepatitis C. Similarly, we reported a 100% SVR in seven patients with severe hepatitis C, four of whom had decompensated cirrhosis . Castells et al reported 100% SVR in six HCV/HIV‐coinfected patients treated with SOF + DCV.…”
Section: Discussionsupporting
confidence: 76%
“…Despite growing data on the safety and efficacy of antiviral therapy in HIV‐negative HCV‐infected LT recipients, data on HCV/HIV‐coinfected LT recipients remain scarce and are based only on small case series . We report the results of the first nationwide, multicenter, prospective case‐control study on the effectiveness and tolerability of antiviral therapy with DAAs in HCV/HIV‐coinfected patients with recurrence of hepatitis C after LT and a matched cohort of monoinfected recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding antiviral treatment of patients awaiting a LT, a study by Londoño et al reported 4 patients with compensated cirrhosis and HCC who received IFN‐free antiviral treatment, all of them achieving SVR and with no tolerability issues. Recently, an Italian multicenter study reported the results of 24 HIV patients with cirrhosis who were treated during the pretransplant period, of whom 20 were decompensated (Child‐Pugh B and C).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 3 out of these 20 patients received peginterferon as part of their therapy. In the previously mentioned study by Londoño et al, 7 HIV‐infected LT recipients received IFN‐free antiviral treatment for severe HCV recurrence, either fibrosing cholestatic hepatitis (FCH), advanced fibrosis (F3), or decompensated graft cirrhosis. All of the patients achieved SVR.…”
Section: Discussionmentioning
confidence: 99%